2012
DOI: 10.1124/jpet.111.188417
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Human Serotonin and Norepinephrine Transporter Occupancy of Duloxetine by Pharmacokinetic/Pharmacodynamic Modeling in the Rat

Abstract: Translation of central nervous system occupancy and clinical effect from animal models to humans has remained elusive for many pharmacological targets. The current studies evaluate the ability of a rodent pharmacokinetic/pharmacodynamic (PK/PD) modeling approach to translate ex vivo occupancy determined in rats to that observed after positron emission tomography (PET) imaging in humans for the dual serotonin transporter (SERT) and norepinephrine transporter (NET) inhibitor duloxetine. Ex vivo transporter occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
3
11
1
Order By: Relevance
“…Although the authors concluded that the estimates of duloxetine sensitivity parameter were similar, the estimated EC 50 in humans was significantly higher than that observed in rats. The mean estimate of EC 50 reported by Takano et al (2006) in humans was 60% higher (3.70 ng/ml) than the mean estimates in humans reported by Abanades et al (2011) (2.29 ng/ml), and in rats reported by Bourdet et al (2012) (2.32 ng/ml). These differences appear to be a consequence of an inconsistent approach to data analysis and PK/PD modeling assumptions between the three reports.…”
Section: Case Study: Pk/pd Model Assumptions In Predicting Human Dulocontrasting
confidence: 46%
See 3 more Smart Citations
“…Although the authors concluded that the estimates of duloxetine sensitivity parameter were similar, the estimated EC 50 in humans was significantly higher than that observed in rats. The mean estimate of EC 50 reported by Takano et al (2006) in humans was 60% higher (3.70 ng/ml) than the mean estimates in humans reported by Abanades et al (2011) (2.29 ng/ml), and in rats reported by Bourdet et al (2012) (2.32 ng/ml). These differences appear to be a consequence of an inconsistent approach to data analysis and PK/PD modeling assumptions between the three reports.…”
Section: Case Study: Pk/pd Model Assumptions In Predicting Human Dulocontrasting
confidence: 46%
“…The authors provided a strong foundation supporting the hypothesis that occupancy of SERT by duloxetine is a translatable biomarker between rats and humans while emphasizing the value of translational PK/PD modeling approaches. Bourdet et al (2012) compared the parameter estimates from their modeling efforts of SERT occupancy in rats to those reported for humans in two literature reports (Takano et al, 2006;Abanades et al, 2011). Although the authors concluded that the estimates of duloxetine sensitivity parameter were similar, the estimated EC 50 in humans was significantly higher than that observed in rats.…”
Section: Case Study: Pk/pd Model Assumptions In Predicting Human Dulomentioning
confidence: 87%
See 2 more Smart Citations
“…From various receptor occupancy, PET imaging studies with clinically approved antidepressants in humans, it has been established that an occupancy of 70-80% is required for the SERT and 50-70% is required for the NET for production of an antidepressant effect [153,[158][159][160]. Also it has been established that to produce a dopamine effect without producing any addiction liability, an occupancy of 30-40% is required for the DAT [161].…”
Section: Proposed Transporter Occupancy For a Trimentioning
confidence: 99%